EXAMINATION OF HOLLAND’S MODEL OF VOCAIONAL INTERESTS USING MULTIDIMENSIONAL SCALING (Annual of the Faculty of Philosophy in Skopje, 2014)
Cross-cultural validation of Holland's theory typically focuses on the structural validity of the R1ASEC model This study examined the structural validity of Hollands model on sample of 207 secondary school students (107 female, all ethnic Macedonians) in the final year of their education. The age range of participants was from 17-19. The similarity of the structure has been explored by using multidimensional scaling method. Results indicate similar structural validity across the samples, especially for the females, although the figures were generally different than those found in previous studies in Western cultures. The identified differences in proximity among various gropus of vocational interests were discussed within the frame of cultural dissimilarities along individualism- collectivism and masculinity-femininity dimensions.
Keywords: MULTIDIMENSIONAL SCALING; STRUCTURAL VALIDITY; HOLAND ’S MODEL OF VOCATIONAL INTERESTS